Transoral 980-nm/1470-nm dual-wavelength fiber laser microsurgery for early-stage glottic carcinoma. (September 2019) - Liang, Faya; Xiao, Zhiwen; Chen, Renhui; Han, Pin; Lin, Peiliang; Huang, Yuzhang; Huang, Xiaoming
Highlights: Transoral laser microsurgery is effective for early-stage laryngeal carcinoma. Clear operative field is helpful to determine the surgical margin accurately. Management of anterior commissure is the key point of Transoral laser microsurgery. Flexible fiber laser with good hemostatic effect can improve the operation fluency and accuracy. Abstract: Objectives: To investigate the effective and safety of transoral 980-nm/1470-nm dual-wavelength fiber laser microsurgery for early-stage glottic carcinoma by compared with CO2 laser surgery. Materials and Methods: From September 2015 to July 2018, 44 patients with early glottic carcinoma underwent transoral microsurgery were divided into 980-nm/1470-nm dual-wavelength fiber laser surgery (Dual-wavelength fiber laser group) and CO2 laser surgery (CO2 laser group). The operative time, number of other hemostatic devices used, postoperative blood loss, surgical complications and postoperative length of hospital stay The time of mucosal epithelialization and Voice Handicap Index-10(VHI-10) in pre-operation, 1-month postoperation and 6-month postoperation in both two groupswere retrospectively analyzed. Results: All the patients underwent successful operation and all the tumors received en-bloc resection with negative margins. The median operative time in Dual-wavelength laser group was faster than CO2 laser group (32.00 min vs 37.50 min, p = 0.014). There was no statistically significant difference between the two groups in the median postoperative hospital stay and the median time of mucosal epithelialization. No patient need feeding tubes place temporarily or permanently in both two groups. Tongue numbness, tear of the palatal arch, postoperative vocal cord adhesion, VHI-10 score in Pre-operation, 1-month postoperation and 6-month postoperation were similar in both two group. No recurrence was reported in both groups during follow-up. Conclusion: Compared to the CO2 laser surgery, transoral 980-nm/1470-nm dual-wavelength fiber laser microsurgery is a safe and feasible procedure for early-stage glottic carcinoma. It can provide clearer surgical field without hemorrhage and make the operation simpler, smoother and faster.